Effects of Combinatorial Ubiquitinated Protein-Based Nanovaccine and STING Agonist in Mice With Drug-Resistant and Metastatic Breast Cancer - Huang, Fang; Pan, Ning; Wei, Yiting; Zhao, Jinjin; Aldarouish, Mohanad; Wang, Xuru; Sun, Xiaotong; Wen, Zhifa; Chen, Yongqiang; Wang, Lixin (Frontiers in Immunology, 2021)
We previously reported that enriched ubiquitinated proteins (UPs) from tumor cells have the potential to be used as immunotherapy vaccine against cancer. Here, we enriched UPs from epirubicin (EPB)-induced multi-drug resistant cancer stem-like breast cancer cell line (4T1/EPB), and tested the efficacy of UPs-4T1/EPB as therapeutic vaccine alone and in combination with the stimulator of interferon genes (STING) agonist in mice with drug-resistant and metastatic breast cancer. Vaccination with UPs-4T1/EPB exerted profound anti-tumor effects through augmented specific CD8+ T cell responses and amplified T cell receptors diversity of tumor infiltrating lymphocytes (TILs). Importantly, combination with STING agonist further facilitated the migration of mature CD8+ DCs to lymph node and infiltration of TILs within tumor, resulting in primary tumor regression and pulmonary metastasis eradication in mice. Moreover, the cured mice were completely resistant against subsequent rechallenge with same tumor. Our study indicates this novel combinatorial immunotherapy with UPs-4T1/EPB vaccine and STING agonist is effective in mice with drug-resistant and metastatic breast cancer.